2015
DOI: 10.13181/mji.v24i2.998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outer dense fiber-1 and -2 protein expression in asthenozoospermic infertile men

Abstract: Background: Most of male infertility are caused by defect in sperm motility (asthenozoospermia). The molecular mechanism of low sperm motility in asthenozoospermic patients has not been fully understood. Sperm motility is strongly related to the axoneme structure which is composed of microtubules and supported by outer dense fiber (ODF) and fibrous sheath (FS) protein. The objective of this study was to characterize the ODF (ODF1 and ODF2) expression in asthenozoospermic infertile male and control normozoosper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous clinical studies have reported a deficiency in outer dense fibers with idiopathic male infertility and asthenozoospermia. 22 23 24 25 However, no ODF2 gene mutation has been previously reported. Could this MMAF case be caused by the mutation in ODF2 ?…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have reported a deficiency in outer dense fibers with idiopathic male infertility and asthenozoospermia. 22 23 24 25 However, no ODF2 gene mutation has been previously reported. Could this MMAF case be caused by the mutation in ODF2 ?…”
Section: Discussionmentioning
confidence: 99%